Alienation effect in Kee Thuan Chye’s Wayang Kulit adaptations in 1984 Here and Now and The Big Purge - Ali Termizi, Arbaayah; Hoo, Poh Ying; Mohd Said, Nur Aainaa Amira; Abdullah Sani, Faris (Universiti Putra Malaysia Press, 2021)
Existing studies have acknowledged the respective influence of Brechtian epic theatre and the adaptation of wayang kulit in Kee Thuan Chye’s plays, though largely keeping them as two separate entities. This paper focuses on Kee’s adaptation of wayang kulit in his first two published plays, namely 1984 Here and Now and The Big Purge to examine its functions in generating the Brechtian alienation effect in the selected plays. The rationales behind the increased scale of wayang kulit adaptation in The Big Purge compared to 1984 Here and Now is also explored in tandem with Kee’s alleged increase in theatrical subtlety. In the findings, the adaptation of wayang kulit in the selected plays correlates to the Brechtian alienation effect through the means of the incongruity of the wayang kulit, the role of the dalang or puppeteer and the fragmented plot structure of the wayang kulit metadrama. In The Big Purge, Kee’s increased scale of wayang kulit adaptation reflects his swerve to a more subtle style of writing as a reaction to the public perception of 1984 Here and Now and his first wayang adaptation in the play.